Analisis Identifikasi Minat Belajar Siswa Sekolah Menengah Atas dalam Pembelajaran Aktivitas Ritmik Melalui Media Audio Visual - Leni Widiawati; Febi Kurniawan; Ega Trisna Rahayu (Peneliti.net, 2022)
The purpose of this study was to determine the level of interest in learning of SMAN 1 Sliyeg students in learning rhythmic activities through audio-visual media for one week. This research is a descriptive study in the form of quantitative data, the method used in this study is a survey method using random sampling technique. Another term for random sampling is one in which all individuals in the target population have an equal chance of voting. The population in this study were all students of class XII IPA SMAN 1 Sliyeg totaling 211 students, the sample obtained was 68 students. Based on the results of the study, it was obtained the percentage that the level of interest in learning of SMAN 1 Sliyeg students in learning rhythmic activities through audio-visual media it could be concluded that overall most of the students of class XII IPA 2, 3 and 4 of SMAN 1 Sliyeg had a high level of student interest in the category of 60.29%.